Implikasi Hukum Kedudukan Wakil Menteri sebagai Penyelenggara Negara Terhadap Larangan Rangkap Jabatan : Legal Implications of the Position of Deputy Ministers as State Administrators Regarding the Prohibition on Holding Dual Positions - Cipta Indra Lestari Rachman; Diani Kesuma; Zulpadli Barus; Salma Nadhifah Ramdhan; Chalisha Albania Rofik (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
The prohibition of deputy ministers holding multiple positions has become a polemic within the government structure due to the absence of explicit legal norms regulating such restrictions. This issue later developed following a Constitutional Court ruling stating that the prohibition on ministers holding multiple positions also applies to deputy ministers. This study aims to examine the legal position of deputy ministers in the Indonesian government system and the legal implications arising from the prohibition on holding concurrent positions. The research employs a normative legal method using statutory and conceptual approaches. Secondary data, consisting of primary, secondary, and tertiary legal materials, are analyzed descriptively and analytically. The study concludes that deputy ministers are state administrators appointed by the President to assist ministers in carrying out their duties and functions. Accordingly, the principles of state administration are inherent in the office of the deputy minister. The prohibition of dual positions has legal implications for interpretation, limits presidential prerogatives, and requires the application of sanctions.